Modeling Infant Mortality in West Pasaman Regency With Negative Binomial Regression to Overcome Overdispersion - Vinna Sulvia; Fitri Mudia Sari; Dina Fitria (UNP Journal of Statistics and Data Science, 2025)
Infant mortality serves as a vital indicator of public health and an essential benchmark of development progress. Although the general trend shows a decline, several sub-districts in West Pasaman Regency continue to report relatively high infant mortality rates, raising concerns about the effectiveness of current health services. This study seeks to examine the determinants of infant mortality using count data regression models. The data were obtained from the publication West Pasaman Regency in Figures 2025 by Statistics Indonesia (BPS), consisting of one response variable, the number of infant deaths, and five independent variables: the percentage of Low Birth Weight (LBW), the proportion of deliveries assisted by medical personnel, the proportion of pregnant women enrolled in the K4 program, the number of health workers, and the number of health facilities. The initial analysis employed a Poisson regression model, which assumes equidispersion, but the results revealed evidence of overdispersion. To address this issue, negative binomial regression was adopted as an alternative approach. Model evaluation using the Akaike Information Criterion (AIC) and the Likelihood Ratio Test confirmed that the negative binomial regression provided a better fit than Poisson regression. The results indicate that the percentage of LBW and the number of health facilities significantly influence infant mortality. Low birth weight (LBW) had a positive association with infant mortality, consistent with theory, while the positive effect of health facilities differed from expectations, possibly due to issues of quality, distribution, or reverse causality.